On the Conceptualisation of LIFE in the melodrama “The Curious Case of Benjamin Button” (2008) - Dale, Inga (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
According to Conceptual Metaphor Theory (hereafter: CMT), conceived by George Lakoff and Mark Johnson (1980), metaphors are not merely rarely occurring poetic or stylistic features of language. On the contrary, as the scholars point out, conceptual metaphors have their origins in our bodily experiences of the world around us. Hence, they are ubiquitous and have a consequently profound influence on our thoughts and actions. This paper aims to show that people, life, love, romance, birth, life stages, life goals, progress made, obstacles along the way, successes and failures, emotions experienced, as well as time, death and the afterlife are conceptualized in modalities of a SOURCE-PATH-GOAL schema, JOURNEY and MOTION IN SPACE domains in accordance with CMT. This is achieved by analysing a monomodal discourse using the Pragglejaz Group (2007) method and an online Cambridge English Dictionary. For the study, I have used a selection of monologues and dialogues of Benjamin Button, the protagonist, together with the characters who have the greatest impact on his life in the Eric Roth screenplay of a melodrama entitled: “The Curious Case of Benjamin Button”, directed by D. Fincher and based on a short story by F. Scott Fitzgerald, featuring Brad Pitt and Cate Blanchett.
Keywords: conceptual metaphor; life; journey; melodrama